Characterization of natural microcosms of estuarine magnetotactic bacteria (2011)
ABSTRACT: To date, no complete study of magnetotactic bacteria’s (MTB) natural microcosms in estuarine or tropical environments has been reported. Besides, almost all the studies around magnetotactic bacteria have been based on fresh waters away from the Equator. In this work, we focused the experimental region at the Equator and present a comprehensive mineralogical and physicochemical characterization of two estuarine bacterial microcosms. The results show that mineral lixiviation in the sediments may be an important factor in the solubilization of elements required by magnetotactic bacteria. Specifically, we show that clinochlore, phlogopite, nontronite, and halloysite could be among the main minerals that lixiviate iron to the estuarine microcosms. We conclude that nitrate concentration in the water should not be as low as those that have been reported for other authors to achieve optimal bacteria growth. It is confirmed that magnetotactic bacteria do not need large amounts of dissolved iron to grow or to synthesize magnetosomes.